Changes in Testing and Treatment Methods in Osteoporosis Care - Takashi Nagai; Koji Ishikawa; Koki Tsuchiya; Soji Tani; Yusuke Dodo; Yusuke Oshita; Keizo Sakamoto; Nobuyuki Kawate; Yoshifumi Kudo (Journal of Osteoporosis)
Osteoporosis treatment plays a crucial role in preventing fractures, particularly in bedridden patients. We conducted a questionnaire survey presenting hypothetical clinical cases in 2015 and 2020 to investigate trends over a 5-year period. The target population included physicians working in clinics and hospitals within our neighbourhood. The cases were presented, and the questionnaire was administered in a confidential format. The orthopaedic surgeons were matched for age and practice, resulting in 74 cases being included in the analysis. Comparing the 2015 and 2020 results, we observed a notable increase in physicians who would perform “bone mineral density measurements of the lumbar spine and hip.” Furthermore, there was a significant rise in the percentage of respondents willing to test for bone metabolic markers, such as serum type I collagen cross-linked N-telopeptide (NTX), procollagen I N-terminal propeptide (P1NP), and tartrate-resistant acid phosphatase 5b (TRACP-5b). Regarding therapeutic agents, bisphosphonates decreased in usage, whereas parathyroid hormone and romosozumab witnessed an increase. In conclusion, the percentage of physicians requesting bone mineral density measurements of the lumbar spine and hip increased over the five-year period. In addition, more physicians chose to utilise bone metabolic markers due to their ease of measurement through blood tests and reduced diurnal variation. Finally, there was a marked trend towards the administration of drugs capable of rapidly and effectively increasing bone mineral density at an early stage of treatment.